Why has home ownership fallen among the young? - Jonas D. M. Fisher; Martin Gervais (Federal Reserve Bank of Chicago, 2010)
We document that home ownership of households with 'heads' aged 25-44 years fell substantially between 1980 and 2000 and recovered only partially during the 2001-2005 housing boom. The 1980-2000 decline in young home ownership occurred as improvements in mortgage opportunities seemingly made it easier to purchase a home. This paper uses an equilibrium life-cycle model calibrated to micro and macro evidence to understand why young home ownership fell over a period when it became easier to own a home. A trend toward marrying later mechanically lowers young home ownership after 1980. We show that the large rise in earnings risk which occurred after 1980 can easily account for the remaining decline in young home ownership.
Keywords: E0; E2; J1; R21; 330; housing; home ownership; tenure choice; first-time home-buyers; marriage; income risk; Wohneigentum; Wohnungsmarkt; Immobilienfinanzierung; Einkommen; Risiko; Ehe; USA